The impact of smart city policy timelinessAnd technology readiness on smart cityPerformance in dubai: The moderating Effect of financial availability - Shwedeh, Fanar F.H (2021)
Unlike any other city, Dubai is proactive in foreseeing the congestion issue popular among the cities. Therefore, the government has embarked on implementing the smart city agenda. Dubai was able to plan and implement Dubai as a smart city that is ranked among one of the world's most performing smart cities in all over the globe. The success of Dubai smart city performance was achieved in a short period of time. However, this contradicts the predominant ideas of smart cities, where most of the earlier smart cities failed to leave beyond the idea stage. On this note, this research identifies some crucial factors that influence smart city performance. These factors are policy timeliness, technology readiness, and financial availability. Policy timeliness and technology readiness are the independent variables. Smart city performance is the dependent variable. Financial availability is introduced as a moderation factor on the relationship between the independent and dependent variables. Due to the movement restriction during the data collection period, the researcher resorts to data collection via an online platform, where an online survey link was sent out to identified and targeted samples which consists of civil servants who contribute one percent (1%) of their monthly salary towards the smart city project. The study employees Partial Least Squares Structural Equation Modeling (PLSSEM) to determine the relationships between the constructs. The results revealed a significant relationship between smart city policy timeliness, technology readiness, and financial availability in ensuring smart city performance. On the contrary, the observed result showed that financial availability fails to moderate the relationship between smart city policy timeliness and technology readiness on smart city performance. The implication of this research showed that financial availability is a crucial factor in ensuring smart city performance.